Exploring virtual reality experiences of slum tourism. Issue 6 (10th November 2022) - Griffin, Tom; Muldoon, Meghan
Abstract: The popularity of slum tourism has been growing and is a topic of substantial discussion. Proponents suggest tours bring awareness and economic opportunity, whereas others critique their voyeuristic nature and claims of community benefits. Virtual reality head mounted displays (VR HMDs) have become relatively accessible in recent years creating a visually immersive experience of a different environment. VR technology is being used by tourism promoters as well as in education and training fields to acquaint people with foreign environments. This exploratory study draws from interviews with 16 participants who declared an interest in slum tourism. Participants discussed their experiences with, perceptions of, and motivations for visiting slum communities, and then watched a VR HMD tour of a slum in Manilla. Immediately following the video participants were asked for reactions and reflections, as well as at a subsequent meeting one to two weeks later. Findings show that the VR HMD was generally positively received, and many participants expressed a sense of trust in the representation of the community and experience because of the media's immersive nature. Participants reported having their understandings of slum communities both reinforced and challenged, leading to more confidence that their awareness of issues in general, and slum tourism specifically, were realistic. Most participants felt more inspired, confident, and comfortable to actually take part in a tour, however some expressed concerns and described feeling less motivated to visit. Discussion includes critique of the video, as well as implications for research and practice.